Comparing the Clinical Effects of Free and Pedicled Flap in Repairing Small Area of Distal Lower Limb Soft Tissue Defects: A Retrospective Comparative Study - Zhe‐Ming Cao; Yan Yang; Li‐Ming Qing; Pan‐Feng Wu; Ju‐Yu Tang (Health Science Reports)
ABSTRACT Background and Aims The exposure of tendons, blood vessels, nerves, and bone due to soft tissue defects in the foot poses a significant challenge for microsurgeons. Free perforator flaps and pedicled perforator flaps are currently the most common methods used for repairing small areas of soft tissue defects in the distal lower limb. Methods A retrospective analysis was carried out on 124 patients with small soft tissue defects in the distal lower limb from January 2009 to December 2021. The evaluation criteria encompassed the patient's intraoperative condition, the occurrence of short‐term and long‐term postoperative complications, as well as the esthetic and functional outcomes. Results In this study, two groups of patients with similar soft tissue defects were included. However, the free perforator flap group showed more severe wound damage compared to the pedicled perforator group. Intraoperatively, the pedicled perforator group needed a larger flap area for wound repair, and the free perforator group had higher intraoperative blood loss and longer operation time. Postoperatively, the incidence of complications was significantly higher in the pedicled perforator group, while the esthetic outcomes were poorer, but the functional evaluation results were better. Conclusion For small soft tissue defects in the distal lower limb, both free perforator flap and pedicled perforator flap are effective in wound repair. The free perforator flap has the advantage of being able to handle more complex wounds with less limitation by location. In cases where the microsurgical expertise is relatively limited and the injuries are minor, pedicled perforator can be considered as the primary choice. Level of Evidence III, case‐control study.